No Association of Leptin Receptor Gene Gln223Arg Polymorphism with Capillary Glucose Levels: A Preliminary Population Base Cross-Sectional Study. (25th August 2013) - Pena, Geórgia das Graças; Guimarães, Andre Luiz Sena; Veloso, Rosângela Ramos; Reis, Tatiana Carvalho; Neto, João Felício Rodrigues; Velasquez-Melendez, Gustavo
Abstract : The leptin receptor gene has been reported to associate with insulin and glucose metabolism and adiposity in different study settings and various populations. Therefore, the aim of the study was to investigate the associations of the leptin receptor gene Gln223Arg polymorphism (LEPR Gln223Arg) with high capillary glucose levels. Cross-sectional study with probabilistic sample was carried out in individuals aged ≥18 years in an urban area of Montes Claros, MG, Brazil. The capillary glucose was considered high when ≥140 mg/dL. The genotypes of LEPR Gln223Arg distribution were as the following: 10.43% GG (n = 49 ), 46.81% AG (n = 220 ), and 42.77% AA (n = 201 ), and there were no prevalence differences between genders, (P = 0.57 ). Multivariate-adjusted models showed that there is no association between the polymorphism LEPR Gln223Arg and capillary high levels of glucose even when adjusted for age, sex, smoking, schooling, and parental history of obesity. In conclusion, no association between the polymorphism LEPR Gln223Arg and elevated blood glucose levels was detected.